Remarks on the deep-sea genus Chalarostylis (Cumacea: Lampropidae) - Alberico, Natalia A.; Roccatagliata, Daniel; Mühlenhardt-Siegel, Ute (Zootaxa, 2014)
Chalarostylis is a deep-sea genus close to Hemilamprops but easily distinguished from the latter mainly by its robust first pereopod. However, this appendage is frequently broken off at the anterior margin of the basis, making the identification of the species of the genus difficult. Regarding Hemilamprops brenkei, both the adult male holotype and the additional specimens herein reported from the Weddell Sea and the Guinea, Argentine and Brazilian Basins exhibit a huge first pereopod. Thus, this species is transferred to Chalarostylis and its description completed. Two other species until now in Hemilamprops, H. canadensis and H. longisetae are also transferred to Chalarostylis. In addition, an unknown species of Chalarostylis from the Bay of Biscay for which no name is given is briefly described. The diagnosis of this genus is emended.